Exploring the Subtle Effect of Aliphatic Ring Size on Minor Actinide‐Extraction Properties and Metal Ion Speciation in Bis‐1, 2, 4‐Triazine Ligands. Issue 2 (30th October 2019) - Zaytsev, Andrey V.; Bulmer, Rachel; Kozhevnikov, Valery N.; Sims, Mark; Modolo, Giuseppe; Wilden, Andreas; Waddell, Paul G.; Geist, Andreas; Panak, Petra J.; Wessling, Patrik; Lewis, Frank W.
Abstract: The synthesis and evaluation of three novel bis‐1, 2, 4‐triazine ligands containing five‐membered aliphatic rings are reported. Compared to the more hydrophobic ligands 1 –3 containing six‐membered aliphatic rings, the distribution ratios for relevant f ‐block metal ions were approximately one order of magnitude lower in each case. Ligand 10 showed an efficient, selective and rapid separation of Am III and Cm III from nitric acid. The speciation of the ligands with trivalent f ‐block metal ions was probed using NMR titrations and competition experiments, time‐resolved laser fluorescence spectroscopy and X‐ray crystallography. While the tetradentate ligands 8 and 10 formed Ln III complexes of the same stoichiometry as their more hydrophobic analogues 2 and 3, significant differences in speciation were observed between the two classes of ligand, with a lower percentage of the extracted 1:2 complexes being formed for ligands 8 and 10 . The structures of the solid state 1:1 and 1:2 complexes formed by 8 and 10 with Y III, Lu III and Pr III are very similar to those formed by 2 and 3 with Ln III . Ligand 10 forms Cm III and Eu III 1:2 complexes that are thermodynamically less stable than those formed by ligand 3, suggesting that less hydrophobic ligands form less stable An III complexes. Thus, it has been shown for the first time how tuning the cyclic aliphatic part of these ligands leads to subtle changes in their metal ion speciation, complex stability and metal extraction affinity. Abstract : Calling all actinides ! Bis‐1, 2, 4‐triazine ligands bearing five‐membered rings were synthesized and evaluated as actinide‐selective extractants. Tuning the size of the aliphatic ring leads to subtle changes in actinide‐extraction properties. The origins of these changes were elucidated at the molecular level, paving the way for the rational design of improved actinide‐selective extractants for reprocessing of spent nuclear fuel.,